How Startups Develop CSR to Build Brand Reputation - Papa, Elena; Daskou, Sofia (My University, 2023)
This paper examines the application of Corporate Social Responsibility (CSR) in building brand reputation and competitive advantage of Cypriot SME startups. It seeks to explore the drivers, importance, and best practice applications of CSR activities by startups. It further analyzes customers' impressions of startup sustainability and CSR practices and the firm's reputation. The study adopted an interpretive study design (thematic analysis), focused on a sample of CSR specialists, advertisers, and startup owners, and revealed a reflection of the theoretical dimension of CSR in the study results. Specifically, the social intensity of CSR implementation and the adoption of practices that focus on human resources, the environment, and society at large, were captured in the data. Basic CRS principles, such as the need for the development and implementation of environmental awareness programs, volunteering, and labor, were commonly agreed by the participants as relevant emerging themes of the study. The results pointed out the importance of company ethics in shaping a healthy employee work environment and highlighted the critical role of the firm's purpose in building the brand. The emphasis on building relationships with society as a whole and specifically with the community in which the company operates seems to be the key to appropriate implementation of CSR regarding brand reputation. The reciprocal relationship created between customers who feel that the company does not solely focus on profit, but center in its connection with the community, is the basis for a profitable course. Voluntary actions organized by the firm to support the community, act as a means of building brand reputation.
Keywords: CSR; Startups; Branding; Reputation Management; Ethics